PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA POP UP BOOK TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR DALAM MATA PELAJARAN IPA - Destiani, Galuh; Asep Kurnia Jayadinata; Nenden Permas Hikmatunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The project-based learning model encourages students to be able to work independently or in groups in constructing learning by creating real products. There are still many who do not know that it is not only critical thinking skills that can be improved in learning, but there are creative thinking skills that must also be improved and developed properly. Learning by only using the lecture method is less effective in improving students' creative thinking skills. Therefore, the project-based learning model can be one of the learning alternatives with the help of pop up book media as a project that will be made by students, can be a creative, concrete, and interesting learning media when doing teaching and learning activities in class. This research method uses a quasi-experimental method with a type of non-evaquivalent control group design. The population in this study were all grade IV elementary school students in Subang sub-district. The samples in this study were class IV A with 24 students and class IV B with 24 students at SD Negeri Cibogo, Subang Regency. The research analysis used T-test, N-Gain, correlation test, and regression test. There is an influence of the project-based learning model assisted by pop up book media on the creative thinking ability of elementary school students in science subjects, giving an influence on the creative thinking ability of students by 18.5%. based on the results of the N-Gain value in the experimental class of 68%, which means that the use of the project-based learning model assisted by pop up book media is stated in the interpretation of effective enough to be used in improving the creative thinking ability of students.